Mechanism Operation for Changing the Rear Axle Clearance of a Universal Row-crop Tractor - A. A. Akhmetov; Sh. A. Akhmedov; B. Zh. Astanov; D. U. Kambarova; R. M. Botirov (Сельскохозяйственные машины и технологии)
The authors noted the disadvantages of the 3-wheel universal row-crop tractor. To eliminate them, LLC Design and Technological Center for Agricultural Engineering developed a 4-wheel universal row-crop tractor with variable ground clearance.(Research purpose) To determine the pressure change in the hydraulic system and the transfer time of the rear axle from one type of clearance to another.(Materials and methods) The authors showed that the rear axle clearance could be changed using a special mechanism - with minimal labor costs, without the use of lifting equipment and assembly and dismantling works. They explained that the mechanism was driven by a working hydraulic cylinder. The experiments were carried out on a prototype tractor with adjustable ground clearance, equipped with a separate-aggregate hinged system at an engine speed of 1200-2000 rpm (revolutions per minute). M10G2K oil was used in the hydraulic system, heating it to 65 degrees Celsius (at an ambient temperature of 33-35 degrees Celsius).(Results and discussion) The hydraulic system consisted of an NSh-32 hydraulic pump, a P80 hydraulic valve, two Ts50-200 working hydraulic cylinders, a double-acting hydraulic lock, a hydraulic tank, filters, hoses and high pressure pipes. At the inlet and outlet channels of the working hydraulic cylinders, which activated the mechanism for changing the rear axle clearance, hydraulic locks were installed, and diaphragm pressure sensors model SS302 from Sendor Sensor with a measurement range from 0 to 40 megapascals were placed along the hydraulic line connecting the hydraulic locks with the hydraulic valve.(Conclusions) The authors determined that the time for transferring the rear axle from low clearance to high was 2.2-4.4 seconds, and the pressure in the hydraulic system was 3.8-16.4 megapascals at an engine speed of 1300-2000 rpm. It was found that when transferring from high to low ground clearance, these indicators amounted to 1.0-1.4 seconds and 0.99-9.90 megapascals.